Method for determining the activity of volume aerosols during communal radiation accident using unmanned aircraft - M. L. Chepur; S. V. Babak; I. P. Marinoshenko; A. V. Morozov; V. Ya. Kanchenko; R. V. Karnaushenko (Ядерна фізика та енергетика)
Analytical analysis of the spread of the radioactive aerosol-based verification of the mathematical model of its movement and deposition was carried out. Nonlinear mathematical model in curvilinear coordinates and on its base the expression for determining the activity of the emission source, using the results of measurements of wind speed with simultaneous fence aerosols filtroejection unit installed on unmanned aircraft was received.